Beyond Infrastructure: Understanding Why Patients Decline Surgery in the Developing World. Issue 6 (December 2017) - Lerman, Benjamin J.; Alsan, Marcella; Chia, Ngew J.; Brown, James A.; Wren, Sherry M.
Abstract : Objective: The aim of this study was to quantify and describe a population of patients in rural Cameroon who present with a surgically treatable illness but ultimately decline surgery, and to understand the patient decision-making process and identify key socioeconomic factors that result in barriers to care. Background: An estimated 5 billion people lack access to safe, affordable surgical care and anesthesia when needed, and this unmet need resides disproportionally in low-income countries (LICs). An understanding of the socioeconomic factors underlying decision-making is key to future efforts to expand surgical care delivery in this population. We assessed patient decision-making in a LIC with a cash-based health care economy. Methods: Standardized interviews were conducted of a random sample of adult patients with treatable surgical conditions over a 7-week period in a tertiary referral hospital in rural Cameroon. Main outcome measures included participant's decision to accept or decline surgery, source of funding, and the relative importance of various factors in the decision-making process. Results: Thirty-four of 175 participants (19.4%) declined surgery recommended by their physician. Twenty-six of 34 participants declining surgery (76.4%) cited procedure cost, which on average equaled 6.4 months' income, as their primary decision factor. Multivariate analysis revealed female gender [odds ratio (OR) 3.35, 95% confidence interval (95% CI) 2.14–5.25], monthly earnings (OR 0.83, 95% CI, 0.77–0.89), supporting children in school (OR 1.22, 95% CI 1.13–1.31), and inability to borrow funds from family or the community (OR 6.49, 95% CI 4.10–10.28) as factors associated with declining surgery. Conclusion: Nearly one-fifth of patients presenting to a surgical clinic with a treatable condition did not ultimately receive needed surgery. Both financial and sociocultural factors contribute to the decision to decline care.